Students’ Error in Transforming Active Voices into Passive Voices in Simple Past Tense - Sari, Ratna; Husnayaini, Ihda; Supiah, Supiah; Sugiarto, Dody (English Education Department, 2022)
This study was carried out to analyze errors made by eleventh grade students in transforming active voices into passive voices. Specifically, it was carried out to identify common errors and obtaining the causes of errors made by the students in transforming active voices into passive voices. The research used descriptive qualitative method. The data were collected through tests and interviews with an English teacher and a number of students. The data test was identified, classified, and analyzed by using Dulay’s surface strategy taxonomy and the causes of errors were analyzed by using Petter Hubbard’s theory. The research revealed two major findings, (1) the most common errors made by students was misformation, which was most frequently produced by the students with a total error of 247 or 52%. It is followed by an error in omission with a total error of 115or 24%. Misordering with 98 errors or 20%, and the lowest is addition with 19 errors or 4%, (2) Based on Petter Hubbard’s theory, mother-tongue interferences, overgeneralization, and error was encouraged by the learning materials and methods used causing those errors.